Pengembangan Metode Komputasi dan Simulasi - Siti Nurul Khotimah; The Houw Liong (Indonesian Journal of Physics, 2002)
In general natural laws, such as Newton's laws, Maxwell's equations, and Schrodinger equation, can be formulated into differential equations. These equations can be modified to be finite difference equation so that they can be solved numerically. Natural laws can also be formulated in the form of least action or Hamiltonian principal then they are solved using finite element method. However, these methods can not be used to solve all of the problems. Scientists developed new computation methods based on the concepts of cellular automata. Each automaton in its internal state will behave as a processor that receives inputs, processes the inputs, determines the next internal state and its outputs. By applying statistical mechanics into cellular automata, this method can simulate earthquake, the process of fluid flows, the process of erosion and sedimentation, and the others. If we look in detail, a nerve cell is an automaton. Therefore the computation method based on artificial neural network can also included as cellular automata method. This means reasoning process, identifying pattern, associative memory, generalisation, and self organising can be simulated using cellular automata method. The computation method based on fuzzy logic also its combination with neural network that is called as Neuro-Fuzzy method can also be viewed as cellular automata method.